A review of theoretical blood flow models - Ortiz-León, Gabriela (2014)
Blood is an incompressible and viscoelastic fluid with Non-Newtonian behavior. A mathematical model should include these features and also must have a compromise between the results accuracy and computational resources need to obtain them. This paper presents a summary of Non-Newtonian models frequently used to describe blood flow, an assessment of diferent bloods models chosen in the literature, a summary of parameters used in blood description and some results obteined from a comparison of blood behavior in an artery.